LITERATUR REVIEW TENTANG SIKAP DAN PENGETAHUAN PETUGAS MEDIS TERHADAP KELNGKAPAN PENGISIAN RESUME MEDIS RAWAT INAP - Handayuni, Linda; Yenni, Ririn Afrima; Mardiawati, Dewi; Yenti, Melda (Ensiklopedia of Journal, 2022)
A medical resume is a summary of all services received by patients during treatment or treatment carried out by health workers. The incompleteness of filling in inpatient medical resumes in hospitals still exists such as lack of attitude and knowledge of health workers, busyness of doctors, absence of SOPs, disagreement with the time limit for filling out medical resumes, which is 1x24 hours. The purpose of this study was to describe the attitudes and knowledge of medical officers to the completeness of filling out an inpatient medical resume. The data used is secondary data, then the data is analyzed by looking for similarities, dissimilarities, views, comparisons and summaries of several research results. The results of the study from 10 journals showed that there were still incomplete medical resumes, due to the lack of knowledge and attitude of officers regarding the importance of completing medical resumes, the unavailability of SOPs for filling out resumes, busy doctors serving patients, resulting in limited time to complete them and the discipline of the doctor in charge. which is still low. From the researcher's analysis, it was concluded that the high number of completeness of completing inpatient medical resumes in hospitals was due to undisciplined officers and the lack of knowledge of officers about filling out resumes. In order to increase the completeness of filling in inpatient medical resumes in hospitals, health workers need to cooperate with each other in filling out medical record documents, especially medical resume sheets in order to create a good, complete and accurate filling.